2015
DOI: 10.1242/bio.013631
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between acoustic habitat, hearing and tonal vocalizations in the Antillean manatee (Trichechus manatus manatus, Linnaeus, 1758)

Abstract: The Antillean manatee (Trichechus manatus manatus) is an endangered marine mammal that inhabits the Caribbean Sea and riverine systems in Central America. Their acoustic behavior is relevant for individual identification, mating and parental care. Manatees produce tonal sounds with highest energy in the second harmonic (usually 5 kHz), and their audiogram indicates sensitivity from 0.3 kHz to 90 kHz with lowest thresholds in the 16 to 18 kHz range. We recorded manatees in the San San River, a highly polluted r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…This could facilitate larger transmission distances of high-frequency signals 60 . However, a recent study found that frequency bands between 0.5-20 kHz have been shown to propagate efficiently in freshwater, marine and brackish habitats for the Antillean manatee and in seagrass beds for the Florida manatee 59,61 . Furthermore, behavioral audiograms identified hearing capabilities ranging from 0.4 to 90.5 kHz with peak sensitivity at 16 to 18 kHz in Florida manatees 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…This could facilitate larger transmission distances of high-frequency signals 60 . However, a recent study found that frequency bands between 0.5-20 kHz have been shown to propagate efficiently in freshwater, marine and brackish habitats for the Antillean manatee and in seagrass beds for the Florida manatee 59,61 . Furthermore, behavioral audiograms identified hearing capabilities ranging from 0.4 to 90.5 kHz with peak sensitivity at 16 to 18 kHz in Florida manatees 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Developing improved methods for detecting endangered species where their populations are in decline is crucial to their preservation. Our previous work illustrated the strength of passive acoustics for detecting manatees, and similar methods have been successful in habitats of the West Indian manatee (LaCommare et al, 2008;Gonzalez-Socoloske et al, 2009;Gonzalez-Socoloske and Olivera-Gomez, 2012;Kikuchi et al, 2013;Rivera Chavarria et al, 2015;Guzman and Condit, 2017;Puc-Carrasco et al, 2017;Castelblanco-Martıńez et al, 2018;Rycyk et al, 2021;Rycyk et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…In addition, manatees produce a variety of vocalizations including squeaks, screeches, whines, and trills (Umeed et al, 2018;Brady et al, 2020;Baotic et al, 2022) shown to be important for their underwater communication and emitted across various behavioral states (Bengtson and Fitzgerald, 1985;O'Shea and Poche, 2006;Brady et al, 2021). Passive acoustics have been used in many studies to monitor manatees and have yielded up to 100% detection frequencies (LaCommare et al, 2008;Kikuchi et al, 2013;Rivera Chavarria et al, 2015;Rycyk et al, 2021;Rycyk et al, 2022). While the above methodologies have been used to monitor other species of manatee (Florida manatees: Rycyk et al, 2022;Antillean manatees: Ramos et al, 2020), they have been rarely implemented with African manatees.…”
Section: Introductionmentioning
confidence: 99%
“…Our detection capabilities were probably hampered by the manatee's elusive nature, and the noise of the engine is likely to have disturbed manatees in the vicinity of the boat, causing them to flee rapidly from the capture area of the side-scan sonar. There is evidence that manatees are capable of localizing the sounds produced by boats (Colbert-Luke et al, 2015), and of reacting to them; for example, disruption of a manatee's call behaviour has been demonstrated at boat–manatee distances of < 25 m (Rivera-Chavarría et al, 2015). As a boat approaches, manatees respond by increasing their swim speed and orienting towards deeper waters (Nowacek et al, 2004).…”
Section: Discussionmentioning
confidence: 99%